A Human Component To Consider In Your Emergency Management Plans: The Critical Incident Stress Factor - Kathleen Madland Kowalski (The National Institute for Occupational Safety and Health (NIOSH))
In recent years the issue of human stress response in emergency workers has begun to receive attention. This paper presents a rationale for considering human stress as a significant factor in the management of emergencies. It discusses the concept of stress, Critical Incident Stress in emergency responders, and introduces the Critical Incident Stress Debriefing (CISD) process. It is suggested that, in a disaster, the CISD process can improve the effectiveness of response teams on site, their turnaround time on site, and post disaster time off the job. This paper, prepared by a US Bureau of Mines research psychologist, offers some ideas to the mining industry in general, mine rescue trainers, and more universally, to those responsible for developing emergency management plans.